2010
DOI: 10.1103/physreve.82.051124
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determination of the bifurcation thresholds in stochastic differential equations with delayed feedback

Abstract: Analytical expressions for pitchfork and Hopf bifurcation thresholds are given for a nonlinear stochastic differential delay equation with feedback. Our results assume that the delay time τ is small compared to other characteristic time scales, not a significant limitation close to the bifurcation line. A pitchfork bifurcation line is found, the location of which depends on the conditional average , where x(t) is the dynamical variable. This conditional probability incorporates the combined effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…Such an effect has been observed previously in scalar non-delayed systems in the presence of multiplicative noise only [26,27,[45][46][47][48]. However, an additive noise-induced transition had been found numerically in a scalar DDE near a Hopf bifurcation [10,49].…”
Section: Insights About Stochastic Systems Stabilitysupporting
confidence: 61%
See 1 more Smart Citation
“…Such an effect has been observed previously in scalar non-delayed systems in the presence of multiplicative noise only [26,27,[45][46][47][48]. However, an additive noise-induced transition had been found numerically in a scalar DDE near a Hopf bifurcation [10,49].…”
Section: Insights About Stochastic Systems Stabilitysupporting
confidence: 61%
“…similar to the single frequency case (48). By virtue of the linearity of the problem, the solution of (51) represents a linear superposition of the solutions (49) for different input strengths and frequencies.…”
Section: Driving At Multiple Frequenciesmentioning
confidence: 99%
“…An approximate expression has been given in [6] in the limit of small delay. We directly integrate Eq.…”
Section: Correlation Timementioning
confidence: 99%
“…It was shown that the location of the bifurcation threshold depends on the intensity of the parametric noise. Analytical approximations for the bifurcation lines have been given in [6] under the assumption that the delay time is small compared to other characteristic time scales of the system. The pitchfork bifurcation line separates exponentially decaying and growing solutions when bτ > −1.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, analytical researches have been concerned with the stability and performance in nonlinear stochastic DDSs, 19 the approximate solutions in nonlinear stochastic systems with small delays, [20][21][22][23] and the dynamical behaviors including resonance and bifurcations. [24][25][26][27][28] Besides, stochastic DDSs are widely used in other fields. For instance, Frank and Beek 29 were dedicated on exploring the biological systems, with the adoption of linear stochastic delay differential equations.…”
Section: Introductionmentioning
confidence: 99%